Current Balancing Design of Paralleled-IGBT in Power Assembly - XIN Lanyuan; SUN Kangkang; GONG Zhe; CHEN Yanping; TANG Longgu (Kongzhi Yu Xinxi Jishu)
It introduced several different types of IGBT paralleling and mainly analyzed influence factors and forming mechanism of current unbalancing in direct IGBT paralleling. From the practical engineering point of view, corresponding design key points were raised on several aspects such as device electrical parameters, junction temperature, gate driver and mechanical structure etc., and they were verified by simulation, double-pulse test and power cycling test. The results show that the power assembly with this design has good current balancing effect.